Living under Surveillance: Cultural Patterns and Their Literary Interpretation in the Soviet Union (KULT_online, 2012)
The influence of the Communist party and the Soviet state on people’s individual living conditions was not necessarily successful. The establishment of certain norms almost automatically implied the attempt to undermine or even violate them. In her dissertation, Sandra Evans interprets one of the most fascinating cultural phenomena of the Soviet city from a perspective of cultural anthropology and literary studies: the life that socially completely different individuals led together in one communal flat, the so called 'Kommunalka'. The basis of her description are literary texts from the 1920s and 1930s that reflect the culture-historical status of a specific form of housing under Stalin’s rule which was a place of communal life as well as an efficacious instance of urban socialization.